2016
DOI: 10.1002/pola.28136
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated poly(meta‐phenylene isophthalamide)s as proton exchange membranes

Abstract: Random and block sulfonated poly(meta-phenylene isopthalamide)s as proton exchange membranes were synthesized through the Higashi-Yamazaki phosphorylation method. Polymers with different degrees of sulfonation from 40 to 100 mol percent were prepared by adjusting the molar feed ratio of 5-sulfoisophthalic acid sodium salt (SIPA) and isophthalic acid (IPA) in the reaction with meta-phenylene diamine. Creasable polymer films were obtained by casting DMSO polymer solutions and the membrane films could be exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Nafion membrane, showing excellent mechanical properties and good chemical stability, is the most frequently used one. Nevertheless, it also presents some drawbacks such as low conductivity at high temperature or low humidity, high cost, and high methanol crossover, which obstruct its wide applications in PEMFCs . Therefore, many aromatic polymer membranes have been developed as alternative PEMs due to their excellent mechanical properties, thermal and chemical stability, high conductivity, and low methanol crossover …”
Section: Introductionmentioning
confidence: 99%
“…Nafion membrane, showing excellent mechanical properties and good chemical stability, is the most frequently used one. Nevertheless, it also presents some drawbacks such as low conductivity at high temperature or low humidity, high cost, and high methanol crossover, which obstruct its wide applications in PEMFCs . Therefore, many aromatic polymer membranes have been developed as alternative PEMs due to their excellent mechanical properties, thermal and chemical stability, high conductivity, and low methanol crossover …”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cell (PEMFC) fueled by hydrogen as a kind of green and efficient energy conversion device has attracted great interests for stationary and mobile applications owing to high power density, high efficiency, low emission power sources, and environmental friendliness . As the key component of PEMFC, proton exchange membranes (PEMs) functioned as a medium to conduct protons from anode to cathode besides acted as a separator between the fuel and oxidant .…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonated aromatic polyamides have also been investigated as potential PEMs for fuel cell technology . For example, Liu and Knauss demonstrated that sulfonated poly(metaphenylene isophthalamide)s with DS of 40% resisted desulfonation at ∼290 °C, a temperature equivalent to SPIs …”
Section: Introductionmentioning
confidence: 99%
“…There are many more examples of sulfonated polymers such as SPIs, [27][28][29][30][31][32][33][34][35][36][37][38][39][40] sulfonated polybenzimideazoles, 41,42 sulfonated polyphthalazinone, 43 and sulfonated aromatic polyamides. [44][45][46][47][48][49][50][51] A recent review by Ghosh and Banerjee 52 covers a specific area of sulfonated fluorinated-aromatic polymers as an example. The aforementioned examples of sulfonated polymers for PEM fuel cell applications show sulfonic acid decomposition in the range of 200-340 8C, depending on molecular architecture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation